Identifying the function of methylated genes in Alzheimer's disease to determine epigenetic signatures: a comprehensive bioinformatics analysis. (2nd February 2021) - Kolay, Sourav; Rahman, Md Rezanur; Islam, Tania; Gov, Esra; Quinn, Julian M.W.; Moni, Mohammad Ali
Abstract: Gene methylation is one means of controlling tissue gene expression, but it is unknown what pathways influencing Alzheimer's disease (AD) are controlled this way. We compared normal and AD brain tissue data for gene expression (mRNAs) and gene methylation profiling. We identified methylated differentially expressed genes (MDEGs). Protein-protein interaction (PPI) of the MDEGs showed 18 hypermethylated low-expressed genes (Hyper-LGs) involved in cell signaling and metabolism; also 10 hypomethylated highly expressed (Hypo-HGs) were involved in regulation of transcription and development. Molecular pathways enriched in Hyper-LGs included neuroactive ligand-receptor interaction pathways. Hypo-HGs were notably enriched in pathways including hippo signaling. PPI analysis also identified both Hyper-LGs and Hypo-HGs, as hub proteins. Our analysis of AD datasets identified Hyper-LGs, Hypo-HGs, and transcription factors linked to these genes. These pathways, which may participate in Alzheimer's disease development, may be affected by treatments that influence gene methylation patterns.